Linking Psychological Ownership to the Entrepreneurial Behaviour of Operational Level Managers in Organizations - Khan, Hassan Haider (2014)
Fostering entrepreneurial behaviour amongst employees has evolved as an important tool for organizations’ survival since it aids their consistent need for improvement, innovation and value creation amid increasing competition (Rigtering & Weitzel, 2013). In an effort to understand how such behaviour comes about, this study set out to examine psychological ownership (organization and job based) as an individual antecedent to the entrepreneurial behaviour of operational level managers and whether organizational citizenship behaviour (organization and individual based) mediated this relationship. Based on a sample of 198 operational level managers working at MNC’s based out of Malaysia, it was found that both forms of psychological ownership are positively related to entrepreneurial behaviour of such employees. Furthermore, this relationship is partially mediated by only one form of organizational citizenship behaviour which is exhibited directly for organizational benefit (OCBO). The findings from this study provide essential direction to future research efforts investigating the effects of individual psychological states and other mechanisms on the entrepreneurial behaviour of employees in established organizations.